The Statistical Thinking Process of Senior High School Students in Solving Data Centralization Problems - Shofi Farihah Muazarah; Nusantara, Toto; Sisworo, Sisworo (Universitas Negeri Semarang, 2025)
This study aims to describe the statistical thinking process of high school students in solving mathematics problems. The method used was descriptive explorative with a qualitative approach, which was conducted at Maarif Lawang High School. The research subjects consisted of 24 students in class X MIPA who had taken statistics material. After being investigated, there were 3 out of 24 students who had solved the problem correctly. Based on the statistical thinking process, it can be grouped into two, namely the complete group and the incomplete group. One person in each group was taken as a group representative. Students completed the test with one data centralization problem. Written exams and in-depth interviews were the means of data collection. The data were next subjected to analysis using data reduction techniques, data display, and the drafting and verification of conclusions. Triangulation techniques were used to assess the veracity of the data. Based on the study's findings, Subject 1 accurately solved the problem and demonstrated proficiency in all four stages of the statistical thinking process: describing data presentation, organizing and reducing data, representing data, and analyzing and interpreting data. Although Subject 2 is capable of finding the proper solution, they are lacking in three key areas of statistical thinking: explaining the presentation of data, organizing and decreasing data, and expressing data.